1977
DOI: 10.2134/jeq1977.00472425000600010023x
|View full text |Cite
|
Sign up to set email alerts
|

Trifluralin Volatilization Losses from a Soybean Field

Abstract: We measured trifluralin (α,α,α‐trifluoro‐2,6‐dinitro‐N,N‐dipropyl‐p‐toluidine) concentrations in air and calculated volatilization losses from a 1.26‐ha field during application at soybean [Glycine max (L.) Merr.] planting and for 120 days after. Air samples, collected at three heights above the soil on 9 days during the season, showed that distinct trifluralin air concentration gradients existed throughout the study with concentrations highest closest to the ground. The highest concentration was measured duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…The maximum volatilization rate of trifluralin was 0.18 mg d-1 at Day 1 and near zero in about two weeks. A similar finding was reported by White et al (1977). The volatilization rate of trifluralin decreased primarily because the surface applied trifluralin was incorporated into the soil.…”
Section: Trifluralin Dynamicssupporting
confidence: 87%
See 3 more Smart Citations
“…The maximum volatilization rate of trifluralin was 0.18 mg d-1 at Day 1 and near zero in about two weeks. A similar finding was reported by White et al (1977). The volatilization rate of trifluralin decreased primarily because the surface applied trifluralin was incorporated into the soil.…”
Section: Trifluralin Dynamicssupporting
confidence: 87%
“…In this study, the model was calibrated using the experimental data reported by White et al (1977). These authors studied trifluralin (α,α,α-reifluoro-2,6-dinitro-N,N-dipropyl-ρtoluidine) volatilization losses from a soybean field at Watkinsville, GA, USA.…”
Section: Model Calibrationmentioning
confidence: 99%
See 2 more Smart Citations
“…During the 38 d prior to the first erosion event on 1991 Oct. 16, only 9 mm of rainfall occurred and the soil surface was relatively dry during this period. Throughout the 140-d period between herbicide application and the first wind erosion event, mean air temperatures were above normal (Table 2) so soil moisture and temperature would have been conducive to both to microbial degradation (Kearney et al 1976;Golab et al 1979;Graper and Rainey 1989a, b) and vapour loss (White et al 1977;Glotfelty 1981;Glotfelty et al 1984;Grover et al 1988;Majewski et al 1993) of trifluralin for much of this period. Vapour loss is one of the main routes of trifluralin dissipation following incorporation into soil and Grover et al (1988) reported a 23.7% vapour loss of trifluralin following soil incorporation at the same study site over a 67-d period in 1983.…”
Section: Environmental Conditionsmentioning
confidence: 99%